2021
DOI: 10.1042/bst20210138
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of vascular smooth muscle cell investment and phenotypic diversification in vascular diseases

Abstract: In contrast with the heart, the adult mammalian vasculature retains significant remodelling capacity, dysregulation of which is implicated in disease development. In particular, vascular smooth muscle cells (VSMCs) play major roles in the pathological vascular remodelling characteristic of atherosclerosis, restenosis, aneurysm and pulmonary arterial hypertension. Clonal lineage tracing revealed that the VSMC-contribution to disease results from the hyperproliferation of few pre-existing medial cells and sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Studies have shown that targeting the vascular tissue with drugs may be effective at modulating and/or preventing neurodegenerative disorders such as AD and PD ( Speer and Ratan, 2009 ; Aguilar-Pineda et al, 2021a ). It has also been suggested that intervening during the differentiation, proliferation, and/or migration mechanisms of VSMCs could be a therapeutic strategy to reduce pathological VSMC functions while maintaining their stabilising roles in CBF ( Worssam and Jørgensen, 2021 ). Here, we will review recent insights on VSMC-based therapeutics in vascular pathology and discuss how VSMCs could be targeted to intervene in the development and progression of neurodegenerative disorders.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Studies have shown that targeting the vascular tissue with drugs may be effective at modulating and/or preventing neurodegenerative disorders such as AD and PD ( Speer and Ratan, 2009 ; Aguilar-Pineda et al, 2021a ). It has also been suggested that intervening during the differentiation, proliferation, and/or migration mechanisms of VSMCs could be a therapeutic strategy to reduce pathological VSMC functions while maintaining their stabilising roles in CBF ( Worssam and Jørgensen, 2021 ). Here, we will review recent insights on VSMC-based therapeutics in vascular pathology and discuss how VSMCs could be targeted to intervene in the development and progression of neurodegenerative disorders.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Abnormal VSMC proliferation is associated with the development of cerebrovascular diseases [ 36 ]. PDGF-BB, the most potent cell proliferation and migration stimulator, initiates cellular responses by activating intracellular signal transduction pathways such as mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK), leading to VSMC proliferation and migration [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PCNA, as an index of cell proliferation, has been identified by immunofluorescence [ 47 ]. During atherosclerosis and intimal hyperplasia formation, various cytokines and growth factors stimulate VSMC to express MMPs [ 31 , 36 ]. In this study, TriL reduced the severity of intimal hyperplasia induced by carotid-ligation and decreased PCNA expression and PDGF-BB-stimulated VSMC migration.…”
Section: Discussionmentioning
confidence: 99%
“…VSMC proliferation is critical in the pathogenesis of atherosclerosis and associated vascular diseases [ 35 , 36 ]. Abnormal VSMC proliferation can be induced by a multitude of mitogenic factors, among which PDGF-BB is the most potent cell proliferation stimulator that acts through the activation of PDGFR signaling and further signal propagation.…”
Section: Discussionmentioning
confidence: 99%